MODEL EUTROFIKASI 2-DIMENSI BERLAPIS UNTUK OPTIMALISASI LOKASI ZONA BUDIDAYA IKAN KARAMBA JARING APUNG (KJA) DI WADUK JATILUHUR - Harsono, Eko (JURNAL BIOLOGI INDONESIA, 2016)
ABSTRACTThe development of floating net aquaculture in Jatiluhur reservoir that reach up 21000 to 26 717 plot have been resulted in eutrophication that interfere of water treatmen raw water, tourism and water sports, so the reduction and redeployment zones floating net in the reservoir needs to be done. The purpose of this study looking for zone of floating net aquaculture in Jatiluhur reservoir. The zone is obtained from the optimization by maximizing the density plots floating net per segment in alternate zones with constraints status trophic allowed in the area of water treatment raw water in take, tourism and water sports in the downstream Jatiluhur reservoir through simulation of the chlorophyll-a concentration distribution from the 2 -dimensional layered eutrophication model for scenarios increase every 10 plots floating net in segments of alternative zones 1, 2, 3 in the downstream reservoirs and alternate zone 4 in the middle of the reservoir. The results of the eutrophication 2-dimensional layered model calculation been obtained segment length and width of 100 m. The optimization results show, the carriying capacity of water due to zoning plots Jatiluhur reservoir floating net per segment in the middle of the reservoir is greater than the downstream of the reservoir, and to get water Jatiluhur reservoir in oligotrophic status that does not interfere with other uses of the reservoir water, and to get water Jatiluhur reservoir in oligotrophic status that does not interfere with other uses of the reservoir water, the highest density of a plot floating net per segment is the alternative zone 4 of 10 plot floating net per segment or 4,420 plot floating net. For the the aquaculture fish in floating net in the area are currently recommended to be moved to alternative zone 4 which is located in the central part Jatiluhur reservoir.Keywords: floating net plot zone, Jatiluhur reservoir, optimalitation, 2-dimensional layered eutrophication